Adult-type rhabdomyoma of the lung: A case report - Yimin Wu; Wenshan Li; Ying Chai (Indian Journal of Pathology and Microbiology)
Adult rhabdomyoma is an uncommon and benign striated muscle tumor consisting of striated muscular tissue. This neoplasm usually originates from cardiac muscle, and extracardiac rhabdomyoma is extremely rare. Herein, we report a case of adult rhabdomyoma in the lung, which has only been reported once in the 1970s. A 62-year-old woman presented to our hospital with a solid nodule on the right upper lobe. We performed tumor resection surgery and confirmed the diagnosis of adult rhabdomyoma by postoperative pathological examination. Herein, we report the clinical and pathologic characteristics of pulmonary adult rhabdomyoma (PAR) and review the literature about adult rhabdomyoma.